Avaliação da obesidade na prevalência e gravidade das disfunções temporomandibulares - Jordani, Paula Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Objectives: Obesity is a chronic and prevalent disorder, comorbid with painful conditions such as musculoskeletal disease. Temporomandibular disorders (TMD) are a high prevalent musculoskeletal pain. The aim of this study was to evaluate the relationship between obesity and the presence and degree of painful TMD. Methods: The sample was stratified according to the presence of painful TMD following the Research Diagnostic Criteria for Temporomandibular Disorders- Axis I and II (RDC/TMD) criteria. The body composition was assessed through Body Mass Index (BMI) and bioimpedance (BIA) analysis. The primary headaches (PH) were classified according to the International Classification for Headache Disorders II (ICHD-II). Uni and multivariate analysis assessed the association between painful TMD and obesity. Results: The sample consisted of 245 individuals (35.89 ± 12.61 years), 183 (74.70%) of them were women. Of the total, 130 (53.25%) presented painful TMD. In contrast with normal weighted individuals, those presenting overweight/obesity according to BIA were more likely to present painful TMD (PR= 1.44, 95%CI= 1.09 to 1.91). Association persisted in multivariate analysis correcting for gender and presence of chronic daily headache (CDH) (OR = 2.02, 95%CI: 1.16 to 3.54). There was no significant association between the grade of the TMD pain and body composition assessed through BMI (p= 0.06) or BIA (p= 0.08). Conclusion: Obesity is associated with the presence of painful TMD, but not with the grade of TMD pain, after adjustment for the CDH and gender.

Objetivo: A obesidade é uma doença crônica, prevalente e comórbida com condições dolorosas como as musculoesqueléticas. A Disfunção Temporomandibular (DTM) é uma dor musculoesquelética altamente prevalente. O objetivo desse estudo foi avaliar a relação entre obesidade com a presença e gravidade de DTM dolorosa. Métodos: A amostra foi estratificada de acordo com a presença e grau de DTM dolorosa de acordo com o Research Diagnostic Criteria para Temporomandibular Disorders-Eixo I e II (RDC/TMD). A composição corporal foi determinada pelo Índice de Massa Corporal (IMC) e pelo exame de bioimpedância (BIA). As cefaleias primárias (CP) foram classificadas segundo critérios da Classificação Internacional de Cefaléia II (CIC-II). Análises uni e multivariadas avaliaram associação entre DTM dolorosa e obesidade. Resultados: A amostra foi constituída por 245 indivíduos (35,89 ± 12,61 anos), sendo 183 (74,7%) mulheres. Do total, 130 (53,25%) apresentaram DTM dolorosa. Houve associação significativa entre a presença de DTM dolorosa e sobrepeso/obesidade avaliada por BIA (RP = 1,44, IC 95% = 1,09-1,91). Associação se manteve em análise multivariada corrigido por gênero e presença de cefaleias crônicas diárias (CCD) (OR= 2,02, IC95%: 1,16-3,54). Não houve associação significativa entre a gravidade de DTM e a composição corporal segundo IMC (p= 0,06) ou BIA (p= 0,08). Conclusão: Obesidade está associada a presença de DTM dolorosa, mas não com a gravidade, após o ajuste para CCD e gênero.
Keywords: Transtornos da articulação temporomandibular; Temporomandibular joint diseases; Obesidade; Fatores de risco